2004
DOI: 10.1902/jop.2004.75.9.1216
|View full text |Cite
|
Sign up to set email alerts
|

TT Virus Infection of Periodontal Tissues: A Controlled Clinical and Laboratory Pilot Study

Abstract: A new DNA virus (TTV) was first identified in the gingival tissue and was found to be significantly associated with the presence of periodontitis. These findings need to be investigated in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…The viral titer was 10 to 10.000 times higher in saliva than in serum. The assumption that TTV might replicate in oropharyngeal tissues and/or salivary glands was supported by the detection of TTV in the gingival tissue [23]. In our study, we found 10 to 1.000 higher viral loads in cervical smears than in the parallel serum samples.…”
Section: Discussionsupporting
confidence: 76%
“…The viral titer was 10 to 10.000 times higher in saliva than in serum. The assumption that TTV might replicate in oropharyngeal tissues and/or salivary glands was supported by the detection of TTV in the gingival tissue [23]. In our study, we found 10 to 1.000 higher viral loads in cervical smears than in the parallel serum samples.…”
Section: Discussionsupporting
confidence: 76%
“…However, the study focused on TTV in general, and genogroup-specific tests were not performed [Rodríguez-Iñ igo et al, 2001]. Interestingly, Rotundo et al [2004] found TTVs (of unspecified genogroups) significantly more frequently in the inflammed gingival tissue of eleven patients with periodontitis than in ten controls without periodontal disease, supporting the above assumption.…”
Section: Discussionmentioning
confidence: 93%
“…A significantly higher salivary occurrence of cytomegalovirus genomes , cytomegalovirus IgG and Epstein–Barr virus antibodies , and of gingival crevice fluid cytomegalovirus IgG , in periodontitis patients compared with healthy subjects, further links the two viruses to destructive periodontal disease. However, studies from Germany and England found low cytomegalovirus, Epstein–Barr virus and herpes simplex virus type 1 copy counts in periodontitis lesions, perhaps because of the type of periodontal disease studied, social and ethnic factors, or disease involvement of different herpesviruses or other types of human viruses . Bacteriophages may also be involved in periodontal disease.…”
Section: Disease Associationsmentioning
confidence: 99%